1999
DOI: 10.1002/(sici)1521-4079(199912)34:10<1239::aid-crat1239>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetic Field in the Kinetics of Crystallization of Diamagnetic and Paramagnetic Inorganic Salts

Abstract: The influence of the magnetic field on some kinetic crystallization parameters of the systems zinc sulfate -water and copper sulfate -water were investigated in a series of controlled batch cooling experiments. The solutions were exposed to magnetic fields with different intensities, up to a maximum of 0.7T. A clear influence of magnetic field on the zinc sulfate crystallization parameters was found: an increase in the saturation temperature, a decrease in the metastable zone width, and increased growth rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…It is proposed that a magnetic field up to 0.5 T would promote the formation of diamagnetic products in eqn (4). According to some related researches, 42,43 the precipitation, nucleation and growth of some inorganic salts can be influenced by an external magnetic field. Freitas et al 42 have found the growth rate of diamagnetic zinc sulfate can be increased by a 0.7 T magnetic field while no effect was observed in the paramagnetic copper sulfate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is proposed that a magnetic field up to 0.5 T would promote the formation of diamagnetic products in eqn (4). According to some related researches, 42,43 the precipitation, nucleation and growth of some inorganic salts can be influenced by an external magnetic field. Freitas et al 42 have found the growth rate of diamagnetic zinc sulfate can be increased by a 0.7 T magnetic field while no effect was observed in the paramagnetic copper sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…According to some related researches, 42,43 the precipitation, nucleation and growth of some inorganic salts can be influenced by an external magnetic field. Freitas et al 42 have found the growth rate of diamagnetic zinc sulfate can be increased by a 0.7 T magnetic field while no effect was observed in the paramagnetic copper sulfate. In addition, the similar phenomena have also been discovered by Madsen and his co-workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth rate of lysozyme crystals was reduced to 60% at 11 T (Yanagiya et al, 2000). But, the increased growth rate and decrease in the metastable zone width under 0.3 T of diamagnetic material was reported by Freitas et al (1999). The experiments were performed under presence of 0.1 T intensity magnetic field, known to have perceptible effect on diamagnetic materials.…”
Section: Introductionmentioning
confidence: 99%